Status of Penaeus monodon Farms, Depots and Processing Industries of Some Selected Areas of Bangladesh (Progressive Agriculture, 2013)
A survey was carried out to evaluate the overall condition, infrastructure facilities, handling and quality management system, condition of raw materials of shrimp, Bagda (Penaeus monodon) farms and depots of some selected shrimp producing areas of Coxs Bazar (Chokoria and Teknaf), Khulna (Paikgacha and Koira), Bagerhat (Rampal and Mongla) and Satkhira (Munshiganj and Ashashuni) through direct observation and interview with cross section of people engaged in farms, depots and processing industries. The survey results revealed that the production of shrimp was not satisfactory. The post-harvest quantitative and qualitative losses in the farms were due to longer duration of harvesting, exposure of shrimp at high ambient temperature for a long time (delayed icing), contamination from dirty floor and lack of general hygiene and sanitation. On the other hand, major quality loss in depots were due to delayed icing, use of inadequate ice, rough handling and peeling, presence of foreign materials, packed under pressure in the bamboo basket, contamination, body crushing, use of dirty utensils and lack or poor personal hygiene of depot workers.DOI: http://dx.doi.org/10.3329/pa.v19i1.17363 Progress. Agric. 19(1): 125 - 134, 2008